Nuclear Power Plants: Innovative Technologies for Instrumentation and Control Systems The Second International Symposium on Software Reliability, Industrial Safety, Cyber Security and Physical Protection of Nuclear Power Plant (Lecture Notes in Electrical Engineering,, 2018)
This book gathers selected papers from the Second International Symposium on Software Reliability, Industrial Safety, Cyber Security and Physical Protection of Nuclear Power Plant, held in Chengdu, China on August 23-25, 2017. The symposium provided a platform of technical exchange and experience sharing for a broad range of experts, scholars and nuclear power practitioners. The book reflects the state of the art and latest trends in nuclear instrumentation and control system technologies, as well as China's growing influence in this area. It offers a valuable resource for both practitioners and academics working in the field of nuclear instrumentation, control systems and other safety-critical systems, as well as nuclear power plant managers, public officials and regulatory authorities.